Pembelajaran Menulis Teks Eksposisi Berfokus Pada Teks Dengan Menggunakan Metode Mind Mapping Pada Peserta Didik Kelas VIII SMP Sumatra 40 Kota Bandung - Silvia Amalia; Eggie Nugraha; Lili Sadeli (Badan Penerbit STIEPARI Press, 2023)
This research is motivated by the low ability of students to write. The purpose of this research is to test the writer's ability to plan, implement, and assess learning to write exposition texts focusing on the structure of the text using the mind mapping method for students in class VIII SMP Sumatra 40 Bandung City; to test the ability of class VIII students of SMP Sumatra 40 Bandung City in writing exposition texts focusing on text structure; to test the effectiveness of the mind mapping method in learning to write exposition texts in class VIII students of SMP Sumatra 40 Bandung City; and to find out the differences in the ability to write exposition texts between students in the experimental class and the control class. In practice the author uses quantitative methods. The data obtained were in the form of pretest and posttest of students from both the experimental class and the control class. The results of this study: 1) The author is able to plan, implement, and evaluate learning to write exposition texts focusing on the structure of the text using the mind mapping method with an average planning score of 3.8 and an average implementation score of 3.9, included in the category Very good. 2) The ability of students in writing exposition texts has increased with an average score of pretest(64.88) (fair category) to posttest (90.36) (very good category). 3) The mind mapping learning method is effectively used in learning to write exposition texts. This is evidenced by the results of the man whitney-u test which revealed the results of Sig. there is a significant difference between the experimental class and the control class. Based on the explanation above, the mind mapping method (concept map) can be used as an effective alternative learning method in writing exposition texts.